Three-Dimensional Metal-Organic Hybrid Material Bearing an Open-Framework Self-Assembled by Mononuclear Cerium Benzene Tetracarboxylate Complex - REN, MIAO-JUAN; ZHANG, ZHONG; ZHAO, PENG; ZHANG, JUN (Asian Journal of Chemistry, 2010)
A kind of novel metal-organic hybrid material formed by stacking and self-assembly of the mononuclear cerium benzene tetracarboxylate complex [Ce(H2btec)½(btec)½(H2O)]n (H4btec = 1,2,4,5-benzene tetracarboxylic acid), simplified as MCBC, has been synthesized under solvothermal conditions (H2O/ acetic acid). MCBC obtained was characterized by differential thermal analysis/thermogravimetry, single crystal X-ray diffraction, elemental analysis and FT-IR analysis. Singlecrystal X-ray diffraction analysis shows that MCBC crystallizes to mononuclear metal carboxylate complex with a 3Dsupramolecular open-framework containing nine-coordinate cerium centers.